Characteristics of Adolescent Intermittent and Daily Smokers - Rubinstein, Mark L. (2014)
INTRODUCTION: Intermittent smoking is common among adolescent smokers, but little is known about adolescent intermittent smokers (ITS). This study describes a cohort of adolescent ITS and compares them to adolescent daily smokers (DS) for the purpose of providing a more detailed characterization of adolescent ITS, specifically patterns of smoking, level of selfreported addiction, and experience with essation METHODS: Participants were 124 ITS and 55 DS. ITS were defined as smoking at least monthly but < 30 days per month; DS as smoking daily. Participants completed demographic, smoking and addiction surveys including the HONC and mFTQ. RESULTS: ITS started smoking at an older age, smoked fewer cigarettes per day and scored significantly lower on addiction scales, but had similar difficulty to DS in quitting smoking with similar numbers of reported quit attempts. These differences remained after adjusting for years of smoking. ITS were more likely to smoke in social situations, while DS were more likely to smoke when angry. Both groups were equally likely to report smoking when drinking alcohol. CONCLUSIONS: We documented significant differences in smoking related behaviors between adolescent ITS and DS. Importantly, we also found that, despite low level infrequent smoking, ITS reported difficulty quitting smoking. Given the risks from light and intermittent smoking, it is essential that we develop a greater understanding of adolescent ITS, including their difficulty quitting and the contextual factors influencing their smoking, so that we may develop new targeted interventions.